Geometric morphometrics and face shape characteristics associated with chronic disease in the elderly (Bioscience Journal, 2018)
The aging process is something that occurs naturally during the lifetime of the human being. It causes biological, psychological and social changes in the body. Anthropometry, which until the late nineteenth century was a common tool in clinical and taxonomic practices, has gained great importance as a public health measure. This methodology is also important in the evaluation of morbidities in individuals and their social practices. Thus, the objective of the present study was to evaluate facial shape characteristics in the elderly, associated with chronic diseases such as diabetes and hypertension, based on two-dimensional images of the lateral and frontal views of the face. Analysis of discriminant function and cross validation presented significant differences (p